Supporting sessional teaching staff in the UK – to what extent is there real progress? - Bryson, Colin (Journal of University Teaching and Learning Practice, 2013)
A major proportion of teaching in UK universities is undertaken by a diverse and large group of sessional staff, in common with many HE systems around the world. This articles reviews efforts over the last decade to support and develop such staff and to improve their situation. Improvement in this area is very slow. The article concludes by considering what progress is likely in the future and the factors and conditions which facilitate or hinder progress.